2016
DOI: 10.1016/j.apjtm.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of dynamic detection for serum levels of MCP-1, TNF-α and IL-8 in patients with acute pancreatitis

Abstract: The dynamic changes of serum levels of MCP-1, TNF-α and IL-8 in patients with acute pancreatitis have their rules, and the change rule of MAP group was different with that of MSAP and SAP group, which showed the reference value for the diagnosis and illness severity evaluation of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
1
11
1
Order By: Relevance
“…TNF-α is a key initiator of pancreatic inflammation (25), and it stimulates acinar cells to increase the release of IL-6 (26,27). The present study demonstrated that the concentrations of serum TNF-α and IL-8 in the MAP group were all lower than those in the SAP group, which was consistent with the results of Yang et al (5) and suggests that TNF-α and IL-8 are strongly associated with the severity of AP. IL-6, which has an important role in the pathogenesis of the disease, may be used as an early predictive marker for AP severity, and its expression level is positively correlated with AP severity (28,29).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…TNF-α is a key initiator of pancreatic inflammation (25), and it stimulates acinar cells to increase the release of IL-6 (26,27). The present study demonstrated that the concentrations of serum TNF-α and IL-8 in the MAP group were all lower than those in the SAP group, which was consistent with the results of Yang et al (5) and suggests that TNF-α and IL-8 are strongly associated with the severity of AP. IL-6, which has an important role in the pathogenesis of the disease, may be used as an early predictive marker for AP severity, and its expression level is positively correlated with AP severity (28,29).…”
Section: Discussionsupporting
confidence: 91%
“…Tumour necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, IL-8 and IL-10 are important inflammatory cytokines markers in the inflammatory development of AP. In a previous study, the changes in monocyte chemoattractant protein (MCP)-1, TNF-α and IL-8 in the serum of the MAP group were different from those of the MSAP and SAP groups, suggesting that the levels of MCP-1, TNF-α and IL-8 are associated with the severity of AP and may serve as diagnostic indicators (5).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…MCP-1 is a family member of the C-C chemokines, and it has been thought to be an important inflammatory mediator in the process of acute pancreatitis and to promote distant organ failure [ 20 , 24 ]. In clinical settings, serum MCP-1 has been reported to increase in patients with complicated acute pancreatitis, and MCP-1 has been thought to play a pivotal role in the pathological mechanism of complicated pancreatitis [ 24 , 25 ]. The results of the present study suggest that MCP-1 could be a predictive and prognostic molecular marker for remote organ injuries and severe pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatitis can essentially be divided into two types: chronic pancreatitis (CP) and acute pancreatitis (AP) [Preiss et al, 2012]. AP can be classified in accordance with the severity of the illness, namely as mild acute pancreatitis (MAP), moderately severe acute pancreatitis (MSAP), and severe acute pancreatitis (SAP) [Yang et al, 2016]. AP is initiated by an acute injury, characterized by an acute inflammatory response that is typically unregulated and disproportional in relation to the extent of tissue injury [Whitcomb, 2010;LaRusch and Whitcomb, 2011].…”
mentioning
confidence: 99%